2008
DOI: 10.1677/erc-07-0192
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced expression of aromatase in p53-inactivated mammary epithelial cells

Abstract: Both the functional loss of p53 and the overexpression of aromatase are important for the progression of breast cancer in postmenopausal women. Here, we found that aromatase expression was up-regulated in primary cultures of mammary epithelial cells (p53 D5,6 MEC) isolated from mice with a defect in exons 5 and 6 of the p53 gene. Aromatase basal activity and expression levels were significantly increased in p53 D5,6 MEC when compared with wild-type MEC. Reporter gene activity in p53 D5,6 MEC transfected with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 40 publications
(27 reference statements)
2
6
0
Order By: Relevance
“…Consistent with our in vitro results, increased Hsp90 ATPase activity, HIF-1␣, PKM2, and aromatase expression were observed in mammary tissues of p53 null compared with p53 wild-type mice. These results are consistent with previous findings demonstrating that aromatase is elevated in p53-inactivated mammary epithelial cells (17). In this previous study, the increase in aromatase was attributed to effects on a known aromatase stimulator, CREB.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Consistent with our in vitro results, increased Hsp90 ATPase activity, HIF-1␣, PKM2, and aromatase expression were observed in mammary tissues of p53 null compared with p53 wild-type mice. These results are consistent with previous findings demonstrating that aromatase is elevated in p53-inactivated mammary epithelial cells (17). In this previous study, the increase in aromatase was attributed to effects on a known aromatase stimulator, CREB.…”
Section: Discussionsupporting
confidence: 93%
“…However, the complex molecular mechanisms underlying the effect of p53 on aromatase expression are poorly understood. In the present study, we have not only confirmed previous results demonstrating that p53 inhibits aromatase expression (16,17) but also have identified a novel mechanism by which this occurs in LFS stromal cells. Importantly, we show that wild-type p53 suppresses Aha1 levels leading to inhibition of Hsp90 ATPase activity.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Two mouse studies have previously examined the relationship between p53 and aromatase. Choi and colleagues (50) found that aromatase was increased in p53-inactivated mammary epithelial cells. The increased phosphorylation and nuclear accumulation of CREB was proposed as a mechanism for the increased expression of aromatase.…”
Section: Discussionmentioning
confidence: 99%
“…Tamoxifen binds to the estrogen receptors (ERs) and suppresses estrogen-dependent breast cancer growth (Iwase et al, 2003). However, serious side effects can occur, including endometrial cancer, thrombosis, and embolism (Choi et al, 2008). Tamoxifen resistance can also be a problem.…”
Section: Introductionmentioning
confidence: 99%